Teacher’s Strategies in Teaching Vocabulary at Vocational High School - Farhana Nur Shobihah; Pratnyawati Nuridi Suwarso; Iswahyuni Iswahyuni (Journey: Journal of English Language and Pedagogy, 2025)
Vocabulary is an important component when learning English because without studying vocabulary, it will be difficult to understand the language. Therefore, effective teaching is necessary for students to comprehend the vocabulary being taught. Teaching strategies can help teachers in teaching vocabulary. This research aimed to identify the strategies used by an English teacher in teaching vocabulary to students at a Vocational High School. A qualitative approach was employed, using semi-structured interviews to collect data from one English teacher at Vocational High School. The results showed that teacher used texts to present the word. Students used printed or online dictionaries to translate the vocabulary found in the texts. The teacher reported no difficulties in applying this strategy. The assessment was conducted by asking questions related to the vocabulary in the texts, and feedback was given after the assessment. The teacher also developed and evaluated the strategies to adapt to the students’ classroom conditions. However, the respondent noted that several students were distracted by the media used during the learning activities. It is suggested that future researchers explore additional vocabulary teaching strategies and offer recommendations for optimizing media use to enhance learning outcomes.